An ultrafast response grating structural ZnO photodetector with back-to-back Schottky barriers produced by hydrothermal growth. Issue 12 (12th February 2015) - Park, Cheolmin; Lee, Jihye; So, Hye-Mi; Chang, Won Seok
Abstract : Nanostructured ZnO UV photodetector produced by UV-NIL with hydrothermal growth achieved ultrafast response time. Abstract : An ultrafast response metal–semiconductor–metal type ZnO ultraviolet photodetector was fabricated by ultraviolet nanoimprint lithography (UV-NIL) with hydrothermal synthesis. The extremely fast response time was due to the Schottky barrier formation attributed to the control of the hydrothermal growth time and grating structure of ZnO, produced by a position-controlled pattering method of UV-NIL. With an on/off frequency of ultraviolet light of 2 kHz using an optical chopper, the device exhibits a rising time of 43 μs and a falling time of 54 μs at a low bias voltage (0.5 V) with a responsivity of 22.1 A W −1 in the active area of 5 × 5 μm 2 . In comparison to other fast response ZnO photodetectors, our device definitely uses easy and low-cost fabrication methods as well as exhibits high performance.